KERJASAMA STAKEHOLDERS PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI DALAM MENGATASI KELANGKAAN KAYU JALUR TAHUN 2019 - Wibowo, Andrian Adi; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Indonesia has many very interesting tourism destinations. The Kuantan Singingi Regency Government is currently trying to preserve the Pacu Jalur Festival. Recently, the people of Kuantan Singingi have found it difficult to find wood to make pathways. Even though spur lanes are a big culture and tradition in Kuantan Singingi Regency that must be maintained. Stakeholder cooperation is urgently needed in efforts to develop or preserve the culture of spur lanes in Kuantan Singingi Regency. The problem that occurs in dealing with the scarcity of track timber is the lack of timber which has a length of 25-30 meters with a diameter of 1-2 meters and has to wait approximately 100 years. If the wood for wood-making materials runs out, it will be replaced with Fiber and will definitely reduce the characteristics of the existing runway path. The research approach used in this study is a qualitative approach and uses descriptive research types. Data collection techniques are interviews, literature studies and documentation. The role of the regional government of the Department of Tourism and Culture is very important, namely the Regional Government as a facilitator, increasing human resources, conducting promotions, and organizing regional events that will increase the awareness of the Community and Indigenous Stakeholders to preserve the culture of spur lanes by protecting customary forests, limiting the taking of jalan timber and fix track. The private sector plays a role as funding for Pacu Jalur and provides tree saplings for materials for making pathways. So that the cooperation that is built by stakeholders well will create communication that is feedback, a well-planned system, fosters a sense of community care which is formed from coaching and supervision. Some of the factors that support handling wood as material for making pathways in preserving the culture of the Pacu jalan festival include: (1) Protecting customary forests, (2) Support from the private sector, (3) Known by domestic and foreign tourists. The inhibiting factors are: (1) The role of local government that is not optimal, (2) Quality of Human Resources, (3) The conversion of forest functions to industrial forests. Keywords: Government, Privat Enterprise, Culture, and Scarcity of Timber